Management of Malignant Pleural Effusions (KYAMC Journal, 2019)
Malignant pleural effusions (MPE) are a common clinical problem in patients with neoplastic disease. In adults, 95% of neoplastic pleural effusions arise from a metastatic source, with lung and breast carcinoma accounting for 75% of all cases. Median survival following diagnosis ranges from 3 to 12 months and is dependent on the stage and type of the underlying malignancy. Most pleural metastases arise from tumor emboli to the visceral pleural surface, with secondary seeding to the parietal pleura. Other possible mechanisms include direct tumor invasion, hematogenous spread to parietal pleura, and lymphatic involvement. Dyspnoea is the most common presenting symptom and is occasionally accompanied by chest pain and cough. Chest radiographs confirm the size and location of the pleural collection. Thoracocentesis is usually diagnostic and also therapeutic. Exudative and hemorrhagic collections should be considered metastatic until proved otherwise. Various modalities are available in the management of MPE. Careful consideration of the patient's expected survival and quality of life is needed when deciding the optimum treatment modality in such patients.KYAMC Journal Vol. 9, No.-4, January 2019, Page 182-189